IMPLEMENTATION OF SMART BOARD MEDIA TO IMPROVE ELEMENTARY SCHOOL MATHEMATICS LEARNING OUTCOMES - Mustanil Mustanil; Abdul Rahman; Dewi Shinta (Sains Global Institut, Indonesia, 2026)
The purpose of this study was to improve mathematics learning outcomes in multiplication and division using smartboard media at Bawakaraeng 1 Elementary School, Makassar City. This type of research is Classroom Action Research (CAR) with 29 students of class IIIa as research subjects. Data collection techniques used were observation, tests, and documentation. This study was conducted over two cycles. Each cycle consisted of two meetings, namely the implementation of learning and the implementation of tests. Each cycle consisted of four stages starting from planning, implementation, observation, and reflection. Data analysis used was quantitative descriptive statistics. The results of this study indicate that student learning outcomes from cycle I to cycle II have increased. In cycle I, the average test result was 76.72 with good criteria, while the test results in cycle II showed an average of 88.34 with very good criteria. Therefore, the implementation of smartboard media is effective in improving elementary school students' mathematics learning outcomes.